The News Value Information Management Training for Local Government Officials of Pangandaran District in 2016 - Aat Ruchiat Nugraha; Agus Rahmat; Trie Damayanti; Anwar Sani (MITRA: Jurnal Pemberdayaan Masyarakat, 2018)
The natural resources potential at Pangandaran has become strategic since its status as a district is definitive. Being a new district, Pangandaran has a number of challenges that must be faced in the era of free trade that is getting closer. That is, it requires qualified skills from the government officials. One of these skills is related to information management for the public. The purpose of this community service is to describe and explain how to improve the knowledge and skills of civil servants engaged in the field of information services in Pangandaran district, especially those related to information management techniques that have news value. The implementation of community service was conducted by lecture, question and answer, and simulation. The results of the activities show that state civil servants engaged in information services for the community in Pangandaran district did not appear to have sufficient knowledge and skills in terms of information management needed by the community. This is evident from the lack of information on the website in government agencies regarding the updating of activities in the district of Pangandaran. Based on our community service activities, we conclude that there has been an increase in knowledge and skills shown by the many questions and discussions of participants on how to find, manage and pack information into valuable news needed by the community. It is suggested that the implementation of community service activities should be in the form of assistance so that speakers would be able to inculcate the values of professionalism in the management of information that is important for the community in Pangandaran district through continuous capacity building and empowerment of professional civil servants in the field of communication.